The generalised extreme value distribution as utility function - Conniffe, Denis (Economic & Social Studies, 2007)
The idea that probability distribution functions could provide appropriate mathematical forms for utility functions representing risk aversion is of respectable antiquity. But the relatively few examples that have appeared in the economics literature have displayed quite restrictive risk aversion properties. This paper examines the potential of the generalised extreme value (GEV) distribution as utility function, showing it possesses considerable flexibility as regards risk aversion properties, even in its single parameter form. The paper concludes that the GEV utility function is worth considering for applications in cases where parametric parsimony matters.
Keywords: Probability distribution; Utility function; Quantitative economics; Risk aversion